THE DETERMINANT FACTORS OF PERSONAL FINANCIAL MANAGEMENT OF INDONESIAN MIGRANT WORKERS IN HONGKONG - Caecilia Wahyu Estining Rahayu; Christina Heti Tri Rahmawati (MIX: JURNAL ILMIAH MANAJEMEN, 2021)
This study aims to examine determinants factors of personal financial management of Indonesian migrant workers in Hongkong. The determinant factors are 1) demographic aspects include age, academic background, number of dependents, and 2) financial literacy. The sample used in this study was several Indonesian migrant workers who are still actively working in Hongkong, especially as household assistants. This study used questionnaire method to obtain the primary data from migrant workers. The sampling technique was non-random sampling which was accidental sampling technique. The data analysis used was Chi-Square analysis. The result shows that: 1) partially, there is relationship between ages and personal financial management; 2) there is a relationship between financial literacy and personal financial management; 3) partially, there is no relationship between academic background and number of dependents with personal financial management. The implication of this study is that by having good knowledge and understanding about finances, Indonesian migrant workers in Hongkong are expected to manage good and wise personal finances, so that they can improve their prosperity.